2011
DOI: 10.1093/rfs/hhr002
|View full text |Cite
|
Sign up to set email alerts
|

Credit Default Swaps and the Empty Creditor Problem

Abstract: School, and the NBER Corporate Finance meetings. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
229
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(242 citation statements)
references
References 32 publications
13
229
0
Order By: Relevance
“…However, at least on average, their presence does not seem to distort the final restructuring outcome toward a higher incidence of bankruptcy. In this respect, our results are consistent with the theoretical predictions of Bolton and Oehmke () who argue that the presence of CDSs does not inevitably lead to an inefficient restructuring outcome.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…However, at least on average, their presence does not seem to distort the final restructuring outcome toward a higher incidence of bankruptcy. In this respect, our results are consistent with the theoretical predictions of Bolton and Oehmke () who argue that the presence of CDSs does not inevitably lead to an inefficient restructuring outcome.…”
supporting
confidence: 91%
“…The concerns regarding the distortive effects of CDSs on debt restructuring may, however, be excessive. Bolton and Oehmke () argue that the presence of insured creditors can have positive or negative effects. On the positive side, CDSs raise the creditors' bargaining power and enable lenders to extract more in debt renegotiations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is expected that the main motivation behind CDS trading is the credit-risk hedging, yet these instruments are traded for manipulation as well. Bolton and Oehmke (2011) discuss a special case in which the debtor buys her own CDSs. This type of trade is defined as the "empty creditor" problem by Bolton and Oehmke.…”
mentioning
confidence: 99%
“…The European Journal of Finance 5 Black (2008) and Bolton and Oehmke (2010), have suggested that the trading of CDS positions results in an empty creditor problem. In this case, the debt holder acquires default protection but retains various control rights in the event of default.…”
Section: Background and Related Literaturementioning
confidence: 99%